2008
DOI: 10.1002/bit.21939
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of onion waste and by‐products: MCR‐ALS applied to reveal the compositional profiles of alcoholic fermentations of onion juice monitored by near‐infrared spectroscopy

Abstract: The overall purpose of the project, of which this study is a part, was to examine the feasibility of onion waste as a support-substrate for the profitable production of food-grade products. This study focused on the efficient production of ethanol from worthless onions by transforming the onion juice into onion liquor via alcoholic fermentation with the yeast Saccharomyces cerevisiae. The onion bioethanol produced could be later used as a favorable substrate for acetic fermentation to finally obtain onion vine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…Likewise, there has been also an increase in demand for processed onions which has led to an increase in waste production (more than 500,000 tonnes annually). Thus, onion producers and processors, regulatory authorities and consumer groups are all interested in developing alternative means for the valorization of the onion waste to promote its proWtable usage and its subsequent conversion into foodgrade products [5]. A possible way to valorize onion waste could be processing them to obtain Wber-rich ingredient, since onion has been recognized as an important source of DF [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there has been also an increase in demand for processed onions which has led to an increase in waste production (more than 500,000 tonnes annually). Thus, onion producers and processors, regulatory authorities and consumer groups are all interested in developing alternative means for the valorization of the onion waste to promote its proWtable usage and its subsequent conversion into foodgrade products [5]. A possible way to valorize onion waste could be processing them to obtain Wber-rich ingredient, since onion has been recognized as an important source of DF [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…They are not suitable as fodder because of their strong characteristic aroma and neither as an organic fertilizer due to the rapid development of phytopathogenic agents such as Sclerotium cepivorum [119]. Their disposal commonly involves landill with high economical costs and important environmental impact [120].…”
Section: Valorization Of Onion By-productsmentioning
confidence: 99%
“…In addition, Multivariate Curve Resolution (MCR) was applied in order to investigate the quality of the NIR spectra and to demonstrate separation of the pure spectrum of water from the pure spectrum of sucrose, as MCR in previous studies has shown a large potential in process monitoring of milk lactic acid fermentation 7 and alcohol fermentation measured with NIR spectroscopy. 8,9 Methods Samples One sample of Milli-Q ® water and 51 samples of Milli-Q ® water with sucrose from 5 % to 55 % (w/w) in 1 % intervals were prepared. In addition, 23 replicates evenly distributed from 5 % to 55 % (w/w) sucrose were prepared giving a total of 75 samples.…”
Section: Introductionmentioning
confidence: 99%